Why Anemia is Associated with Increased Mortality in AECOPD, What Should We Do? [Letter] - Zhou TT (International Journal of COPD)
Ting-Ting Zhou Lanzhou University Second Hospital, Lanzhou, People’s Republic of ChinaCorrespondence: Ting-Ting Zhou, Lanzhou University Second Hospital, Cuiyinmen 82, Chengguan District, Lanzhou, Gansu, 730030, People’s Republic of China, Email zhoutt20@126.com